Computational analysis of Nitinol stent-graft for endovascular aortic repair (EVAR) of abdominal aortic aneurysm (AAA): Crimping, sealing and fluid-structure interaction (FSI). (1st April 2020) - Jayendiran, Raja; Nour, Bakr; Ruimi, Annie
Abstract: Objectives: We evaluate the crimping strain, sealing stress and contact forces on a Nitinol stent deployed in the aorta during endovascular aortic (or aneurysm) repair (EVAR) procedures. Nitinol shape memory effect (SME) is used. We also study the fluid-structure interaction (FSI) of the blood flow on the stented aorta. Methods: We employ Solidworks to generate a closed-cell honeycomb stent structure used to treat abdominal aortic aneurysm (AAA). We use the commercial Abaqus/Simulia finite element (FEM) simulation package to study the displacements and stresses experienced by the stent during the crimping phase and deployment into the aortic segment. The Nitinol stent is covered with Dacron, a popular graft material. We implement our own user-material (UMAT) subroutines to model the shape memory effect (SME) of Nitinol. The effect of the stent geometry is analyzed. We use the FSI analysis in Abaqus/Simulia to understand the effect of hemodynamic loading on the stent. Results: Results indicate that the crimping strain increases as the stent strut spacing increases. This is also the case for the radius of curvature. Maximum strains developed on the stent during crimping are in the order of 10%. Stresses exerted by the stent needed to completely seal the aorta are found to be below the yield stress values of Nitinol (700 MPa). Wall shear stresses (WSS) on the stented aorta are close to WSS obtained on the aorta alone. Conclusion: Using Nitinol's thermo-reactivity property as opposed to its superelasticity causes the stent-graft to deploy more gently. Highlights: The stent geometry (strut spacing, radius of curvature) affects the crimping strains The stent as designed will not fracture The stented aortic segment generates stresses close to those on a healthy aorta The stent adheres well to the aortic walls and migration is unlikely to occur Nitinol thermoreactivity is advantageous compared to when using superelasticity